Characteristics of wetland flora in Dong Thap Muoi nature reserve, Tien Giang province - Manh Huong, Kieu; Thi Hanh, Nguyen; Thi Luong, Nguyen; Van Hop, Nguyen (Journal of Forestry Science and Technology, 2023)
This study aimed to analyze the floral attributes of Dong Thap Muoi Nature Reserve in Tien Giang province. Findings revealed the presence of 136 vascular plant species spanning 113 genera and 53 families within the Polypodiophyta and Angiospermatophyta phyla. These species manifest in six primary life forms: trees, shrubs, vines, herbs, epiphytes, and palms. Notably, the flora demonstrates significant utility, encompassing seven categories of beneficial plants: medicinal plants, edible plants, ornamental plants, tannins-dyes, essential oils, poisonous plants, and other valuable types. Moreover, two species, Elaeocarpus hygrophilus Kurz and Oryza rufipogon Griff, classified as Vulnerable in the Vietnam Red Data Book (2007), are noteworthy for their conservation importance. Six plant dominant associations further distinguish the area’s vegetation as Melaleuca cajuputi Maton & Sm. ex R.Powell, Stenochlaena palustris (Burm.f.) Bedd., Bambusa pallida Munro.Voss, Bambusa multiplex (Lour.) Raeusch. ex Schult.f., Ficus microcarpa L.f., and Salvinia cucullata Bory. These associations play a crucial role in providing habitat, foraging, and nesting grounds during the breeding season for various species. The study suggested that effective long-term conservation strategies should focus on preserving the existing floral diversity. Concurrently, efforts should be made to prioritize selecting and introducing indigenous tree species in reforestation programs to rehabilitate depleted zones or enhance vegetative cover on barren lands.